COVID-19 and Monetary Response of Reserve Bank of India: A Critical Review - Kumar Bijoy; Shivam Shaurya (Archives of Business Research, 2021)
The unprecedented shocks from the COVID-19 pandemic jeopardized the global economy and created an environment of Knightian uncertainty all around. This study evaluates the impact of the monetary policy responses initiated by Reserve Bank of India (RBI) to mitigate the cascading effect of the pandemic on Indian Economy. The study uses a combination of exploratory and analytic approach for evaluating the monetary policy responses initiated since January 2020. Actions of RBI are analysed under four headings namely Policy Rate Cuts, Liquidity Provisions and Credit Supports, Asset Purchases, and Regulatory Easing. It is observed that RBI has responded on all four fronts successfully which are evident through availability of sufficient liquidity and easy credit in the market for all the stakeholders like central and state governments, large corporates, MSMEs and individuals. RBI must maintain the momentum of policy response till the return of normalcy in the economy. It should also be ensured that no adverse effect appears after withdrawal of the stimulus extended as policy response against the pandemic.